KEARIFAN LOKAL MASYARAKAT PANGKALAN INDARUNG DALAM PENGELOLAAN LUBUK LARANGAN SEBAGAI RANCANGAN MODUL BIOLOGI SMA - Sandria, Jeky; ', Suwondo; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Research was conducted to determine the Local Wisdom Base Village Society Indarung resources management in a river in the village of Pangkalan Indarung, Kuantan District Subdistrict Singingi Singingi in April until the month of May 2016. The research used to design a modular unit at study Biology with the concept of Biodiversity Conservation in SMA, in two stages namely stage of research and design stage module unit. Collecting data using in-depth interviews with snowball sampling technique with key informants that indigenous leaders (Datuk Pudako Kayo) and village heads Indarung Base. Also used methods of observation and documentation techniques. The results showed there were some local knowledge possessed by the people of the village of Pangkalan Indarung resources management in river, among others, 1) The planning stage, the village of Pangkalan Indarung have wisdom in the use of fishing gear as well as the timing of harvesting. 2) The use, in this context, the villagers Pangakalan Indarung utilize the resources of the river in the form of fish wisely. 3) Control, in this case the Base Village community Indarung use the event starting reinforcements to preserve the resources of the river. 4) Maintenance, to perform certain tree planting activities on the river bank to prevent abrasion on the edge of the river. 5) Supervision, formed a community group watchdog organizations and traditional institutions in the supervision Tuah Sukato depths of the ban. 6) The law enforcement with sanctions for any violators of customs rules, sanctions in the form of community sanctions. The results of this study can be used as an ingredient in designing learning modules on the concept of Biological Biodiversity Conservation.